Bacterial Communities and Culturable Petroleum Hydrocarbon Degrading Bacteria in Marine Sediments in the Northeastern South China Sea - Xu, Wenhui; Qiao, Yanlu; Wei, Jinxiao; Jiang, Qing; Xue, Jianliang (Frontiers in Environmental Science, 2022)
Marine oil spill pollution is one of the factors affecting the marine ecology of the northeastern South China Sea (nSCS). The submarine oil produced after the oil spill have a long-term impact on the microbial community in the sediment. In this study, to learn the distribution and activity of low-temperature petroleum hydrocarbon degrading bacteria in sediments of the nSCS, 16S rRNA genes high-throughput sequencing and quantitative PCR were performed; meanwhile, petroleum hydrocarbon degrading bacteria were isolated and their activity were detected. The results show that the bacterial functional genes in the sediments will be affected by petroleum hydrocarbons, and reflect that the pollution of organic matter in the eastern part of the sea is more serious than that in the western part. This may be related to the migration of organic matter caused by ocean currents and submarine landslides. More low-temperature petroleum hydrocarbon degrading bacteria are isolated from deep-sea sediments. Among the strains with better performance, the diesel degradation rate for 5 days at 10°C is about 45%. Based on previous studies on the SCS, this study further proved the factors affecting the spatial distribution of bacterial communities in the sediments, and confirmed the degradation ability of potential petroleum hydrocarbon degrading bacteria.